PARAMETER KINETIKA INAKTIVASI TERMAL DAN ISOLASI Staphylococcus aureus PADA MINUMAN DARI GEL CINCAU HIJAU DAN ROSELA - Eko Hari Purnomo; Puspo Edi Giriwono; Dias Indrasti; Antung Sima Firlieyanti; Andini Giwang Kinasih (Jurnal Teknologi dan Industri Pangan, 2015)
Information about heat resistance (D and z values) of target bacteria is needed for the thermal process design on drink from Green Grass Jelly (Premna oblongifolia Merr.) and Roselle (Hibiscus sabdariffa L.), so it can guarantee quality and safety of the product. The objectives of this research were to isolate Staphylococcus aureus from commercial green grass jelly and to determine the D and z values of Staphylococcus aureus (from commercial product and standard clinical isolate ATCC 25923) on heating menstruum of green grass jelly and roselle. Isolation of S. aureus was done by inoculation in selective medium, D and z values of Staphylococcus aureus were assessed by heating at constant temperatures of 57, 53, 49, and 45°C during the time interval 2.5, 5, 10, and 15 minutes. The results showed that one isolate (Isolate A) gave positive response of Staphylococcus aureus in isolation tests and had similar percentage with the reference culture of 41.8% using the API Staph Kit. Heat resistance of Staphylococcus aureus (represented as D value) isolated from green grass jelly at constant heating temperature of D45, D49, D53 and D57 were 32.3, 17.9, 4.6, and 1.5 minutes. On the other hand, D value of isolates ATCC 25923 (standard clinical isolate) at constant heating temperature of D45, D49, D53 and D57 were 18.5, 6.8, 2.9, and 1.4 minutes. The z value of isolates A and ATCC 25923 were 8.8°C and 10.8°C. Smaller z value of isolate A showed that pasteurization process can be accelerated and optimized with increasing the temperature slightly but has the same lethality effect.